PEDOMAN ISLAM DALAM KEHIDUPAN ORGANISASI DAN PROFESI - Sitti Nur Annisa Muharyati; Dahlan Lama Bawa (STKIP Subang, 2026)
In the increasingly complex world of organizations and professions, the integration of Islamic values is crucial to ensure that organizational goals are not solely focused on achieving results but also on moral and spiritual aspects. This paper aims to identify Islamic ethical principles relevant to organizational and professional life, as well as how their implementation can be applied in the modern workplace. The study reveals the challenges faced in applying Islamic values within organizations and professions and provides strategies to overcome these challenges. Islamic life guidelines such as trustworthiness (amanah), honesty, justice, and contributions to the common good serve as the main foundation that can be applied in organizational and professional life to foster integrity and ethics aligned with Islamic teachings.